Ex-prisoners and the labour market in the Czech Republic - Klára Kantová (Charles University in Prague, Institute of Economic Studies (IES), 2023)
This study investigates the effect of ex-prisoners on the unemployment rate at times of low rate of unemployment as well as examines the effect of the unemployment rate on the recidivism rate in the Czech Republic during the period 1992-2018. The Czech Republic has a significant issue with the extensive scale of its prison population, which places a great burden on the Czech economy. Ex-prisoners also represent a cost for the state as they receive social benefits. Another big concern in the Czech Republic is the recidivism rate which reaches huge values every year, ranging from 57% to 75% in the period 1992-2018. To prevent recidivism, it is important to reintegrate released prisoners back into society. In this study, I use the data provided by the Prison Services Yearbooks as well as the data from the Czech Statistical Office. The results indicate no significant effect of released prisoners on the unemployment rate. Further, the results show that when there is a 1% rise in the unemployment rate, it causes an almost 1.1% rise in the recidivism rate.
Keywords: J7; J21; J65; 330; unemployment rate; ex-prisoners; recidivism rate; Czech Republic; regions